The Description of St. Sophia Cathedral in Constantinople by Michael of Thessaloniki: Russian Translation and Commentary - Vinogradov, Andrey Yu; Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2016)
The paper is dedicated to the Greek description of St. Sophia of Constantinople written in mid-12th century by Michael of Thessaloniki, Byzantine intellectual and the head of Patriarchal school. He participated in the theological disputes of his time and was condemned for heresy. Michael’s description of St. Sophia is known from the only manuscript in Escorial. The text’s final part seems to be missing. We publish the first Russian translation of this text with some comments on the realities mentioned by Michael, as well as on his literal sources. In a manner similar to that of a guide, Michael presents to his audience the different aspects and parts of the building: its view from the outside, atrium, narthex, naos, colonnades, vaults, walls, floor, the altar, ciborium, solea, ambo, etc. The text turns out to be a sort of rhetorical exercise demonstrating the erudition of the author. He describes different aspects of the building from the point of view and in the language of different branches of science and art: rhetoric, geometry, optics, theology, poetry, cosmography, petrology, painting, exegesis. The text is filled with quotations from the previous classic and Byzantine authors, in particular those who wrote other descriptions of St. Sophia (Procopius of Caesarea, Paul the Silentiary).